2013
DOI: 10.1371/journal.pone.0054684
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study on the Development of Cross-Reactive Neutralizing Antibodies in HIV-1 Infected Individuals

Abstract: Broadly neutralizing antibodies may protect against HIV-1 acquisition. In natural infection, only 10–30% of patients have cross-reactive neutralizing humoral immunity which may relate to viral and or host factors. To explore the role of host genetic markers in the formation of cross-reactive neutralizing activity (CrNA) in HIV-1 infected individuals, we performed a genome-wide association study (GWAS), in participants of the Amsterdam Cohort Studies with known CrNA in their sera. Single-nucleotide polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 33 publications
1
22
1
Order By: Relevance
“…Several groups have tested the neutralizing activity in a large group of samples on different virus panels and reported that screening for a reduced panel (6 viruses or less) of selected viruses provided similar information on the presence of cross-reactive neutralizing activity as screening for a large virus panel (30)(31)(32)(33). The broadly neutralizing activity of the patients selected with our 6-virus panel was also confirmed previously with an extended panel, including 25 additional viruses from different subtypes (15).…”
Section: Neutralization Breadth Stability In Bcrn and Control Patientssupporting
confidence: 72%
“…Several groups have tested the neutralizing activity in a large group of samples on different virus panels and reported that screening for a reduced panel (6 viruses or less) of selected viruses provided similar information on the presence of cross-reactive neutralizing activity as screening for a large virus panel (30)(31)(32)(33). The broadly neutralizing activity of the patients selected with our 6-virus panel was also confirmed previously with an extended panel, including 25 additional viruses from different subtypes (15).…”
Section: Neutralization Breadth Stability In Bcrn and Control Patientssupporting
confidence: 72%
“…To this end, various studies have attempted to identify signatures within HIV-1 Env or clinical/host factors that correlate with the development of breadth [10,21,22,31,36,38,69,77,88], on the basis that they could be targeted by immunization strategies. We postulated that factors present as early as several weeks after infection could also be determinants for subsequent development of breadth, as early Env diversity was previously linked with breadth [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the ability to produce bNAbs is determined by host genetic factors, but there are as yet no studies that support this hypothesis (Euler et al, 2013). An alternative possibility, first suggested by studies in macaques, is that the initial envelope sequence that the immune system encounters is an important determinant of whether or not neutralization breadth develops (Shingai et al, 2012; Walker et al, 2011b).…”
Section: Vaccination To Produce Anti-hiv-1 Neutralizing Antibodiesmentioning
confidence: 99%